2020
DOI: 10.3390/bs10040073
|View full text |Cite
|
Sign up to set email alerts
|

IMPULSE Moment-by-Moment Test: An Implicit Measure of Affective Responses to Audiovisual Televised or Digital Advertisements

Abstract: IMPULSE is a novel method for detecting affective responses to dynamic audiovisual content. It is an implicit reaction time test that is carried out while an audiovisual clip (e.g., a television commercial) plays in the background and measures feelings that are congruent or incongruent with the content of the clip. The results of three experiments illustrate the following four advantages of IMPULSE over self-reported and biometric methods: (1) being less susceptible to typical confounds associated with explici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…This theory provides a framework with which to understand the adoption of neuromarketing by companies. In the last decades, there has been a "boom" in the use of neuroscience methods for commercial purposes, mainly in areas such as television and advertising (Crespo-Pereira and Legerén-Lago, 2017;Harris, 2019;Calvert et al, 2020). A review of the existing literature, however, suggests that large enterprises seem to resist implementing neuromarketing techniques, due to the impact of a series of internal and external factors (Crespo-Pereira et al, 2016;Spence, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory provides a framework with which to understand the adoption of neuromarketing by companies. In the last decades, there has been a "boom" in the use of neuroscience methods for commercial purposes, mainly in areas such as television and advertising (Crespo-Pereira and Legerén-Lago, 2017;Harris, 2019;Calvert et al, 2020). A review of the existing literature, however, suggests that large enterprises seem to resist implementing neuromarketing techniques, due to the impact of a series of internal and external factors (Crespo-Pereira et al, 2016;Spence, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Neuromarketing reveals information that is not provided by traditional qualitative and quantitative techniques in order to predict consumers preferences (Hubert and Kenning, 2008;Plassmann et al, 2012Plassmann et al, , 2015. In the last decades, there has been a "boom" in the use of neuroscience methods for diverse commercial purposes, mainly in areas such as television and advertising (Crespo-Pereira and Legerén-Lago, 2017;Harris, 2019;Calvert et al, 2020). Advertising and media have always tried to apply new technologies for a better understanding of the human brain in order to create more effectiveness in campaigns and content, however the term neuromarketing was not coined at the very first moment.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we exploited two implicit reaction time tasks. The first, the recently developed Impulse test, is a novel implicit reaction time paradigm that measures the moment-to-moment shifts in emotions when, for example, people are viewing dynamic videos or footages [34]. The second is a task based on affective priming, a very well established implicit paradigm that was developed out of cognitive psychology in the 1980s [41,42,43] and has been recently adapted for use in commercial neuromarketing studies [35].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research has shown that the speed and accuracy of classification of these words reflect the feelings that a participant has towards the content of the movie or television clip [34]. By comparing reaction times to classify positive and negative emotional words during the training (baseline) and experimental phase, it is possible to infer the nature of the internal feelings elicited in the viewer by the video content every 2 s. Specifically, we have found that positive emotions elicited by the footage shown, speeds responses to positive words and slows them to negative ones.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation